Optimizing bioethanol production via consolidated bioprocessing: the potential of Aspergillus niger B2484 - Mona Fatin Syazwanee Mohamed Ghazali; Muskhazli Mustafa; Nur Ain Izzati Mohd Zainuddin; Nor Azwady Abd Aziz (Penerbit Universiti Kebangsaan Malaysia, 2025)
Consolidated bioprocessing (CBP) integrates enzyme secretion, hydrolysis, and fermentation into a single-step process, eliminating the need for costly separate enzyme production in bioethanol manufacturing. While CBP aims to utilize naturally occurring cellulolytic microbes, no single microorganism has been identified to efficiently perform all required processes. One of the key challenges in CBP is optimizing culture conditions to maximize bioethanol yield. This study investigates the potential of Aspergillus niger B2484 as a single-culture bioethanol producer and optimizes the physicochemical parameters for converting pretreated paddy straw into bioethanol through CBP. Key parameters, including saccharification and fermentation duration, temperature, substrate loading, and medium composition, were evaluated using the One-Factor-At-a-Time (OFAT) method and further optimized via Response Surface Methodology (RSM). The optimal conditions were determined to be 66.7 hr of saccharification at 29.8°C, followed by 32.3 hr of fermentation at 30.2°C, with a substrate loading of 2.6% (w/v) and a medium level of 14.8% (v/v). The actual ethanol yield (0.63 g/L) closely matched the RSM-predicted yield (0.61 g/L), confirming the reliability of the optimization model. This study demonstrates the feasibility of A. niger B2484 as a single-culture bioethanol producer in CBP, highlighting its potential for commercial application either as a standalone microbial agent or as part of a customized enzymatic system to enhance bioethanol yield.